When Walking is Suffering and Travel an Irony: The Pain of Central Americans Passing Through Mexico - Vázquez Vázquez, José Dionicio (2019)
The aim of this paper is to present the risks and abuse that Central American migrants have faced through Mexico, which inhibit their purpose of reaching the United States. The most relevant results of research show that police and gangs in Mexico have extorted and robbed the Central American migrants. Some institutions that did not support them in their transit were the Human Rights Commission, churches, non-governmental organizations and prosecution authorities. At the same time, they recognize the support of refuges and residents of some localities of Tlaxcala who do not perceive them as a risk to the safety of their families. The methodology of the study was a qualitative approach, using semi-structured questionnaire interviews, with Central American migrants and residents from municipalities of the State of Tlaxcala.